Transcriptional evolution underlying vertebrate sexual development. Issue 4 (28th November 2012) - Valenzuela, Nicole; Neuwald, Jennifer L.; Literman, Robert
<x xml:space="preserve">Abstract</x> Explaining the diversity of vertebrate sex‐determining mechanisms ranging from genotypic (GSD) to temperature‐dependent (TSD) remains a developmental and evolutionary conundrum. Using a phylogenetic framework, we explore the transcriptional evolution during gonadogenesis of several genes involved in sexual development, combining novel data from Chrysemys picta turtles (TSD) and published data from other TSD and GSD vertebrates. Our novel C. picta dataset underscores Sf1 and Wt1 as potential activators of the thermosensitive period and uncovered the first evidence of Dax1 involvement in male development in a TSD vertebrate. Contrasting transcriptional profiles revealed male‐biased Wt1 expression in fish while monomorphic expression is found in tetrapods but absent in turtles. Sf1 expression appears highly labile with transitions among testicular, ovarian, and non‐sex‐specific gonadal formation patterns among and within lineages. Dax1's dual role in ovarian and testicular formation is found in fish and mammals but is dosage‐sensitive exclusively in eutherian mammals due to its X‐linkage in this group. Contrastingly, Sox9 male‐biased and Aromatase female‐biased expression appear ancestral and virtually conserved throughout vertebrates despite significant heterochronic changes in expression as other elements likely replaced their function in early gonadogenesis. Finally, research avenues are highlighted to further study the evolution of the regulatory network of sexual development. © 2012 Wiley Periodicals, Inc. Developmental Dynamics 242:307–319, 2013. © 2012 Wiley Periodicals, Inc.